SUBSTITUSI SEBAGIAN RANSUM DENGAN MINYAK KELAPA TERHADAP PERFORMAN AYAM KAMPUNG SUPER PETELUR - Rori, Yobel; Najoan, Marie; Leke, Jein R.; Imbar, Meity R. (Universitas Sam Ratulangi, 2019)
SUBSTITUTION OF SOME RATION WITH COCONUT OIL ON THE PERFORMANCE OF LAYING SUPER NATIVE CHICKEN. The pupose of the research is to knowing the substitution of some ratio with coconut oil on the performance of laying super native chicken. this research already implemented during 8 weeks. The material used in this study was a 80 laying hens super native chicken aged 5 month. The research design used was the completely randomized design (CDR) with 5 treatment and 4 replications. Tukey test was used for further test. Treatments were formulated as follow : R0 = 100% control diet + 0% Coconut Oil (CO); R1 = 99.5% control diet + 0.5% CO; R2 = 99% control diet + 1% CO; R3 = 98.5% control diet + 1.5% CO; R4 = 98% control diet + 2% CO. The result showed that applying the coconut oil until 2% giving increase for egg production and giving the same effect for feed consumtion and feed conversion.Keywords : laying super chicken native, coconut oil.